2022
DOI: 10.1186/s40510-021-00396-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of bruxism on maxillary arch length and width in children using three-dimensional digital model analysis

Abstract: Background Bruxism is defined as repetitive jaw-muscle activity characterized by the grinding and clenching of teeth. The prevalence of bruxism in children is extensive, and it can cause irregularities in dental arches. The study aimed to investigate the presence of any effects of bruxism on maxillary arch length and width in children using three-dimensional (3D) digital model analysis. Method This study evaluated 30 children with bruxism. For ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Similarly, whehn the measurements were combined between the left and right sides, the results showed the same results between bruxism and non-bruxism patients. In line with research of Hazar et al, 21 there was no significant difference in terms of the arch length and width in children with and without bruxism.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, whehn the measurements were combined between the left and right sides, the results showed the same results between bruxism and non-bruxism patients. In line with research of Hazar et al, 21 there was no significant difference in terms of the arch length and width in children with and without bruxism.…”
Section: Discussionsupporting
confidence: 90%
“…(p = 0.656). In a similar line of research, Hazar Bodrumlu et al [40] found that the length and width of the maxillary arch in child patients are not associated with bruxism. However, the scientific literature reports an association between bruxism and the presence of dental crowding [41].…”
Section: Association With Diastemas and Dental Crowdingmentioning
confidence: 85%
“…Emodi-Perlman et al have reported that habits such as pacifier use and onychophagia increase the likelihood of a child developing sleep bruxism. Therefore, healthcare professionals are advised to be vigilant in identifying clinical signs of bruxism in children who exhibit or have a history of pacifier use and nail-biting [40]. These habits have been suggested to increase the risk of bruxism due to repetitive oral movements and increased muscle activity in the jaw and face.…”
Section: Association With Orofacial Factors and Habitsmentioning
confidence: 99%
“…Although the etiology of this condition is still unclear, certain factors, such as temporomandibular joint disorders, stomatognathic system dysfunction, bruxism, mental disorders, or excessive use of chewing gum are thought to be involved; unilateral occurrence can be seen when patients chew or clench primarily on one side [ 8 , 9 , 10 ]. Bruxism may be a risk factor of malocclusion, generating higher forces due to the increased activity of the masticatory muscles; bruxism may also cause some alterations in the dimensions of the maxilla, leading to a larger palate, causing facial asymmetry and masticatory muscle hypertrophy [ 11 ]. Oral submucous fibrosis, a pre-malignant condition, also may manifest with masseter muscle hypertrophy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%